Indigenous vegetables: consumer and market vendor preferences in Cavite, Philippines - Gonzales, Bambi; Chavez, Hidelisa D. de; Sister, Lorna E; Anunciado, Ma. Shiela; Monville-Oro, Emilita; Gonsalves, Julian Francis; Hunter, Danny; Borelli, Teresa; Mendonce, Sharon (2023)
Indigenous vegetables (IVs) are locally-adapted, nutritious and culturally significant crops, yet consumption of IVs is low- with dwindling numbers of people with knowledge about their multiple uses and benefits. Additionally, in urban areas such as the Cavite province in the Philippines, IVs are not easily found in markets- the place where most households acquire their vegetables from. Improving IV consumption requires concerted efforts both on the supply and demand side of the IV value chain, based on a clear understanding of consumer and market vendor preferences.